EFFECT OF LOW INTENSITY AEROBIC EXERCISE ON VO2PEAK OF WOMEN WITH BREAST CANCER UNDERGOING CHEMOTHERAPY - Novayanti, Etta; Wardhani, Indrayuni Lukitra; Narasinta, Inggar; Suprabawati, Desak Gede Agung; Pratiwi, Niken; Soebadi, Ratna Daryanti (Folia Medica Indonesiana, 2025)
Breast cancer treatments, particularly chemotherapy, have been associated with significant declines in cardiopulmonary fitness, a key determinant of functional independence and survival. VO2peak, a marker of cardiopulmonary function, is often reduced in patients undergoing chemotherapy, increasing morbidity risks. Researchers have proposed exercise interventions to mitigate these effects. However, most studies focused on moderate-to-high-intensity regimens, with limited data on the efficacy of low-intensity aerobic exercise. This study aimed to explore the impact of low-intensity cycle ergometer aerobic exercise on VO2peak in women undergoing chemotherapy for breast cancer. A randomized controlled trial with twenty participants randomly assigned to an intervention group (n = 10, low-intensity aerobic exercise twice per week for 8 weeks) or a control group (n = 10, usual care). VO2peak was estimated using the 30-Second Sit-to-Stand (30STS) test. Statistical analysis was performed using paired and independent t-tests, with effect size (Cohen’s d) calculated to assess clinical significance. The intervention group demonstrated a significant increase in VO2peak (Δ= +1.93 mL/kg/min, p < 0.001), while the control group showed a non-significant change (Δ= +0.25 mL/kg/min, p = 0.31). Between-group analysis suggested a significant difference in favour of the intervention (p = 0.02, Cohen’s d = –2.56), indicating a large effect size.